2‐Pentylfuran: a novel repellent of Drosophila suzukii. Issue 4 (14th December 2020) - Cha, Dong H; Roh, Gwang H; Hesler, Stephen P; Wallingford, Anna; Stockton, Dara G; Park, Shinyoung K; Loeb, Gregory M
Abstract: BACKGROUND: Drosophila suzukii (Matsumura), spotted‐wing drosophila (SWD), is a major invasive pest of soft‐skinned fruits in North America and Europe. Although insecticides are currently the primary method of SWD control, it is imperative to develop alternative management approaches, such as behavioral control through the use of repellents and attractants. This study explores the repellent properties of 2‐pentylfuran as an oviposition deterrent on raspberries. RESULTS: 2‐Pentylfuran was found to be aversive to SWD in laboratory multiple‐choice tests. When co‐released from a vial (loaded as neat compound) with a synthetic SWD lure, 2‐pentylfuran reduced SWD attraction to the SWD lure by 98% and the effect appeared 17% stronger compared to 1‐octen‐3‐ol, a known SWD repellent. Releasing 50% 2‐pentylfuran mixed with mineral oil from a vial located near ripe raspberries resulted in 30% reduction in SWD oviposition in the field. In laboratory no‐choice assays, 2‐pentylfuran reduced SWD oviposition on raspberries above 2.5 mg h −1 with greater repellency achieved at higher release rates. A release rate of 10 mg h −1 from a polyethylene sachet reduced egg‐laying on raspberries by 60% in a semifield cage choice experiment. In a field experiment using fruiting raspberry clusters, 14 mg h −1 release rate of 2‐pentylfuran was effective at reducing SWD infestations by 56% compared to untreated plots. CONCLUSION: 2‐Pentylfuran acts as a repellent for SWD and can significantly reduce fruit infestations under field conditions and high SWD pressure. Given that 2‐pentylfuran is a registered food additive and generally regarded as safe, 2‐pentylfuran has a potential use in behavioral control strategies against SWD. Published 2020. This article is a U.S. Government work and is in the public domain in the USA Abstract : This study demonstrates the novel use of 2‐pentylfuran, a natural scent of plants and microbes, as a repellent for Drosophila suzukii, which can significantly reduce fruit infestations under field conditions. Published 2020. This article is a U.S. Government work and is in the public domain in the USA